The Scenario of Brand Management Aspects Adopted By Leading MNCs in Bangladesh: An Investigative Study - Hamid, Dewan Afrida (Indonesian Journal of Business and Entrepreneurship, 2024)
Background: The aspect of brand management has been reinforced in the multinational organizations in Bangladesh in the recent couple of decades. Purpose: This article investigates strategic and tactical initiatives to find a rigorous picture in the field of branding of well-established MNCs running their functions in Bangladesh. Design/methodology/approach: The data for this study have been elicited from ten worldknown MNCs that have always maintained top national ranking in the country. Exploratory research method and purposive sampling have been applied herein to analyze the data. Findings/Result: The findings show the growing importance of brand management through a range of strategic branding variables adopted by the prominent MNCs working in Bangladesh. On the whole, this article imparts knowledge of the crucial set of brand management phenomena that serve as the deciding factors for naming, renaming, and diversifying brands as it is becoming increasingly influential to take control of the extremelycompetitive market. Conclusion: As per the findings in this study, in order to excel in today’s market, it is crucial for all branding managers of the concerned companies to prioritize branding management and its strategic approaches. While the circumstances regarding brand duality are satisfactory, there is potential for substantial enhancement, which could yield positive outcomes. Originality/value (State of the art): This study explores the brand management strategies employed by major multinational companies (MNCs) operating in Bangladesh and evaluates g the statistical context of brand management tactics within the sampled companies. Keywords: brand name, branding strategies, branding tactics, brand management, mismanagement of brand, Bangladeshi MNCs